2015
DOI: 10.1016/j.hrthm.2015.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Real-time atrial wall imaging during radiofrequency ablation in a porcine model

Abstract: An IVUS probe coupled to an RF catheter can provide relevant real-time imaging of the atrial wall during ablation. Although thickness change does not appear as a good predictor of the transmural extent, direct visualization and monitoring of RF application may provide new information to guide and secure RF ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…In the preexperimental study, we confirmed that lesions were obscured when the sections were stained with hematoxylin and eosin. As described in the previous experiment, 18,19 lesions and nonablated tissue were identified by Masson's trichrome stain as blue and red portions, respectively. Hence, the sections were stained with Masson's trichrome.…”
Section: Pathological Lesion Assessmentmentioning
confidence: 99%
“…In the preexperimental study, we confirmed that lesions were obscured when the sections were stained with hematoxylin and eosin. As described in the previous experiment, 18,19 lesions and nonablated tissue were identified by Masson's trichrome stain as blue and red portions, respectively. Hence, the sections were stained with Masson's trichrome.…”
Section: Pathological Lesion Assessmentmentioning
confidence: 99%
“…Development of non-invasive real-time monitoring methods is hence essential for optimizing outcomes of these treatments. To this end, several imaging modalities have been suggested for this purpose [7][8][9][10][11]. However, these are either limited by lack of contrast and sensitivity, the use of ionizing radiation, shallow penetration or insufficient spatio-temporal resolution [8,12].…”
Section: Radiofrequency (Rf) Catheter Ablation Is Widely Employed Formentioning
confidence: 99%
“…Other imaging modalities that were explored for ablation lesion monitoring are conventional ultrasound [12][13][14][15] as well as ultrasound elastography [16][17][18]. Visibility of lesions on grayscale ultrasound has been disputed in literature, with contradictory reports of both decrease and increase in echogenicity in lesion areas.…”
Section: Rf Ablation Lesion Imaging In the Literaturementioning
confidence: 99%